Strategi Guru Bahasa Indonesia dalam Mengimplementasikan Kurikulum Merdeka di SMPN 1 Tompobulu Kabupaten Bantaeng - Tenriola, Gina; Mayong, Mayong; Haliq, Abdul (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study examines the strategies of Indonesian language teachers in implementing the Independent Curriculum at SMPN 1 Tompobulu, Bantaeng Regency. The purpose of the study is to describe the planning, implementation, and assessment strategies of Indonesian language teachers in implementing the Independent Curriculum at SMPN 1 Tompobulu, Bantaeng Regency. The type of research is qualitative with a descriptive qualitative approach design. Data collection techniques through interviews with two Indonesian language teachers, classroom observations, and document analysis. The data analysis technique in this study uses analysis according to Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that the strategy of Indonesian language teachers in the planning stage has considered aspects of mature planning and student needs. At the implementation stage, teachers have used teaching tools by referring to teaching modules, and at the assessment stage using a comprehensive assessment of learning. This study concludes that the implementation of the Independent Curriculum has shown success in creating effective and meaningful learning for students.